Effects of Problem Based Learning on Mathematics Performance, Instructional Efficiency and Affective Attributes In Secondary Schools, Port Dickson, Malaysia - Abdullah, Nur Izzati Lojinin (2009)
Problem Based Learning (PBL) is an engaging instructional strategy in which students are given ‘triggers’ or realistic, simulated problems that are puzzling, vague or ambiguous before they experience any instruction in a specific content area. Previous research had discovered that students are trained to develop critical thinking, are adaptable to change, able to work independently, demonstrate effective communication skills and become continual learners through PBL. A quasi experimental study with non-equivalent control group posttest only design was conducted to investigate the effects of PBL on Form Four Malaysian students’ mathematics performance and instructional efficiency. The experiment was carried out for six weeks involving 53 Form Four students randomly selected from the district of Port Dickson. The experimental group (n=29) were exposed to the to the PBL instruction whereas the control group (n=24) were taught conventionally. There were five instruments used in this study namely, a posttest, Paas Mental Effort Rating Scale, learning assessments during the acquisition phase, a questionnaire on perception towards group work, interest in mathematics and perception towards mathematics learning experience and a rubric evaluating students’ effective use of Polya’s problem solving procedures, mathematical communication and teamwork. The results indicated that there was no significance difference in the mean scores of the overall mathematics performance (F =1.46, p > .05) between the PBL group (M=67.38, SD=19.75) and the CT group (M=60.58, SD=17.90). On the other hand, there was a significance difference in mean mental effort per test problem for the PBL group (M=5.02, SD=1.60), and the CT group (M=3.90, SD=1.38; t (51) =2.70, p < .05). An independent sample t-test conducted on the mean relative condition efficiency index showed that there was no significant difference (t (51) = -1.70, p < .05) between the PBL group (M= - 0.26, SD=1.26) and the CT group (M = 0.32, SD=1.22). The findings of the study showed that the PBL group used the Polya’s problem solving procedures more effectively, displayed better mathematical communication skills and showed stronger teamwork compared to the CT group. However, minimal differential effect on mathematics performance and instructional efficiency was obtained between the PBL and CT group. Hence, this indicated that the efficacy of PBL has yet to be explored in enhancing mathematical performance and to develop problem solving skills, critical thinking and communication skills among learners. Overall, the PBL instructional strategy has promising implications in teaching and learning of Form Four mathematics specifically in enhancing thinking and communication skills among learners in order to develop critical, creative and competent human capital with first-class mentality who are able to face and overcome the challenges of globalisation in Malaysia.